The Potential of Soursop Seed Extract Annona muricata Linn as a Biopesticide against Aphids Aphis gossypii Glover (Homoptera: Aphididae) on Chilly - Abdullah, Fauziah; Sina, Ibnu (Malaysian Journal of Science, 2003)
Aphids of the fourth instar of $Aphis$ $gossypii$ were subjected to toxicity test against 80,000 ppm, 60,000 ppm, 40,000 ppm, 20,000 ppm, 10,000 ppm, 5,000 ppm, 1,000 ppm of seed extract of $Annona$ $muricata$. Diathion 1,000 ppm and water were used as control. 59% aphids mortality was reached within 24 hours for the 80,000 ppm concentration whereas 50% mortality occurred only 48 hours after application for the 60,000 ppm concentration. For the 40,000 ppm and 20,000 ppm concentrations, 48% and 52% mortality were reached after 72 hours and 120 hours after application respectively. The ladybird beetle $Epilachna$ $indica$ (Coleoptera: Coccinelidae) exposed to 80,000 ppm and 40,000 ppm response stock extract showed toxic response 48 hours after application while the symbiont ant $Oecopylla$ $smaragdina$ (Hymnoptera: Formicidae) was not affected. This study shows that the extract of $Annona$ $muricata$ seed has potential as a biopesticide against aphid pests of vegetable species in Malaysia.Aphids of the fourth instar of $Aphis$ $gossypii$ were subjected to toxicity test against 80,000 ppm, 60,000 ppm, 40,000 ppm, 20,000 ppm, 10,000 ppm, 5,000 ppm, 1,000 ppm of seed extract of $Annona$ $muricata$. Diathion 1,000 ppm and water were used as control. 59% aphids mortality was reached within 24 hours for the 80,000 ppm concentration whereas 50% mortality occurred only 48 hours after application for the 60,000 ppm concentration. For the 40,000 ppm and 20,000 ppm concentrations, 48% and 52% mortality were reached after 72 hours and 120 hours after application respectively. The ladybird beetle $Epilachna$ $indica$ (Coleoptera: Coccinelidae) exposed to 80,000 ppm and 40,000 ppm response stock extract showed toxic response 48 hours after application while the symbiont ant $Oecopylla$ $smaragdina$ (Hymnoptera: Formicidae) was not affected. This study shows that the extract of $Annona$ $muricata$ seed has potential as a biopesticide against aphid pests of vegetable species in Malaysia.